Blueberry benefits to cognitive function across the lifespan. (4th July 2021) - Bell, Lynne; Williams, Claire M.
Abstract: It is well known that what we eat can influence our physical wellbeing, but interest is also increasing in the relationship between our diet and cognitive health. In recent years, blueberries have risen from relative obscurity to superfood status following a number of published epidemiological studies, rodent trials, and human RCTs, that suggest blueberries may convey benefits to cognition and mood. This commentary explores some of the evidence in humans, particularly during periods of cognitive development in the young and cognitive decline in the elderly. Evidence for possible mechanisms of action are also described. There is little doubt that blueberries convey a small, but tangible, benefit to cognitive function. Effects are seen following dose sizes easily achievable within a normal diet. Nevertheless, further research is needed on the cognitive domains influenced, additional benefits of longer-term supplementation, mechanisms of action responsible, and the real-world relevance of the cognitive benefits attained.